Students’ perspectives on wheelchair basketball in mainstream and special schools - Greve, Steffen; Süßenbach, Jessica (Frontiers in Education, 2022)
Very little research has been done on students' perspectives on sports courses in special schools. The state of knowledge about students' perspectives on concrete teaching concepts in inclusive physical education (PE) at mainstream schools is almost as incomplete. The present study was designed to address these two desiderata. For this purpose, a teaching concept was developed that was implemented in the PE lesson of one class in a mainstream school and in two sports courses in two special schools. Following this, guided interviews were conducted with 19 students: four boys and four girls from the mainstream school and 10 boys and one girl from the special school. The interviews were analyzed using grounded theory coding techniques. The students' views differed strongly between the different school types. The students in the mainstream school expressed themselves very positively about the content of wheelchair basketball, but they saw sitting in a wheelchair as a very deficient activity. The students at the special school did not express the same opinion. However, it became clear that the special school was a microcosm that provided a sanctuary for the students. Leaving this comfort zone, for example, to join a wheelchair basketball club, could be very difficult for them. Mainstream school students, however, found learning opportunities in this context: They discovered a new perspective, namely, that of a person with disabilities, even if only for a very short time.